Influence of the leukoreduction moment of blood components on the clinical outcomes of transfused patients in the emergency department - Natasha Dejigov Monteiro da Silva; Ana Catharina Herbst; Milena Raquel André; Lilia de Souza Nogueira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to investigate the influence of the leukoreduction moment (preor post-storage) of blood components on the clinical outcomes of patients transfused in the emergency department. Methods: retrospective cohort study of patients aged 18 years or older who received preor post-storage leukoreduced red blood cell or platelet concentrate in the emergency department and remained in the institution for more than 24 hours. A generalized mixed-effects model was applied in the analyses. Results: in a sample of 373 patients (63.27% male, mean age 54.83) and 643 transfusions (69.98% red blood cell), it was identified that the leukoreduction moment influenced the length of hospital stay (p<0.009), but was not dependent on the transfused blood component (p=0.124). The leukoreduction moment had no effect (p>0.050) on transfusion reactions, healthcare-associated infections, or mortality. Conclusions: patients who received pre-storage leukoreduced blood components in the emergency department had a shorter length of hospital stay.